THE PERFORMANCE OF THE OFFICIALS SECRETARIAT DPRD - Nandang Krisna Saktiokta (Solidaritas, 2018)
AbstractResearch on the performance of the officials Secretariat DPRD Kota Surakarta, aims to describe how the performance of the officials Secretariat REGIONAL city of Surakarta. This event will be based on research by the DPRD Secretariat employee performance in carrying out the tasks and functions, which are listed on the Mayor of Surakarta Regulations No. 27c Year 2016. Research method in this research is descriptive qualitative. The collection of data in this study through observation, interview and documentation. Technical analysis data analysis techniques used are interactive.This research uses the theory of Soedarmayanti (2010) about performance measurement and use Regulations the Mayor No. 2016 year 27C about the position, Organization, duties, functions, the Device Work Area of the city of Surakarta. In the theory of performance measurement indicators is divided into 4 indicators, among others, work achievement, skills, behaviors, and cooperation. The overall Performance of the employees of the Secretariat REGIONAL city of Surakarta is already good enough. As a suggestion from the aspect of 4 need for a work placement in accordance with the educational background. Then the level of discipline or leadership officer should also be improved because an employee of the Secretariat has been implementing REGULATION (Peraturan Pemerintah) No. 53 years 2010 chapter I and chapter II of the discipline of civil servants. Need for resolute action to indisipliner actions performed repeatedly. Furthermore need enhanced sense of responsibility employees remain in working in spite of labor contracts that helped him. Keywords: Performance, Employees, The Secretariat.